Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/electronics9101617
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Drusen Segmentation for Age-Related Macular Degeneration in Fundus Images Using Deep Learning

Abstract: Drusen are the main aspect of detecting age-related macular degeneration (AMD). Ophthalmologists can evaluate the condition of AMD based on drusen in fundus images. However, in the early stage of AMD, the drusen areas are usually small and vague. This leads to challenges in the drusen segmentation task. Moreover, due to the high-resolution fundus images, it is hard to accurately predict the drusen areas with deep learning models. In this paper, we propose a multi-scale deep learning model for drusen segmentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The issue of poor image quality has also been mentioned by other works 38,39 . The pretrained drusen segmentation model that we used was trained on high‐quality CFPs with a resolution of 1200 × 1200 36 …”
Section: Classification Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…The issue of poor image quality has also been mentioned by other works 38,39 . The pretrained drusen segmentation model that we used was trained on high‐quality CFPs with a resolution of 1200 × 1200 36 …”
Section: Classification Resultsmentioning
confidence: 84%
“…On the public dataset (n = 6565), the proposed method achieved a mean (SD) sensitivity of 0.58 F I G U R E 3 Examples of inaccurate drusen masks generated by on the Ocular Disease Intelligent Recognition (ODIR) dataset. 36 Row 1: colour fundus photographs; Row 2: generated drusen masks. We observed that the drusen masks contain many false-positive pixels and may lead models to focus on the wrong regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two sizes were appropriate for completing the network training while occupying fewer computing resources and preserving the features and details of the images to some extent. 25 , 26 Data augmentation was used in the training stages to simulate the uncertainty in the image acquisition process by means of giving the augmented image the same label as the original image.…”
Section: Discussionmentioning
confidence: 99%
“…In the end, an FC layer was established that classified input pairs into Wet AMD, Dry AMD, PCV, and nAMD. Another work was proposed, based on drusen segmentation for AMD detection, by Pham et al [143] where they tried to tackle the data imbalance problem, as the number of non-drusen pixels was very high compared to drusen pixels. Their model consists of two networks, one an Image level network that uses a Deeplabv3+ base architecture to generate drusen probability maps and a patch-level network that works on corresponding patch images and their probability maps for final prediction.…”
Section: Amd Diagnosismentioning
confidence: 99%